Examining the Relationship Among Economic Growth, Exports and Total Productivity for OECD Countries Using Data Envelopment Analysis and Panel Data Analyses - Hüseyni, İbrahim; Eren, Miraç; Çelik, Ali Kemal (MONTENEGRIN JOURNAL OF ECONOMICS, 2017)
The main objective of this paper is to explore the relationship between Total Factor Productivity (TFP) and economic growth and exports for OECD countries for the sample period 1990-2013. For this purpose, firstly, TFP values were calculated using data envelopment analysis (DEA) for the corresponding countries within the availability of their labor force and fixed capital formation data for the relevant sample period. Secondly, several panel data analyses were performed to determine the impact of TFP values on economic growth and exports of OECD countries. Consequently, results reveal a statistically significant positive impact of TFP on both economic growth and exports for OECD countries.
Keywords: Total factor productivity; Data envelopment analysis; Economic growth; Panel data analysis